The Impact of Shipping Costs, Market Competition, And Service Quality with Exchange Rate as a Moderating Variable on the Export Volume in Shipping Companies - I Gede Srineka Kawibawa; Lira Agusinta; Edhie Budi Setiawan; Eduard Alfian Syamsya; Sarinah Sihombing (Dinasti Review, 2026)
This study examines the effects of shipping costs, market competition, and service quality on export volume, with the exchange rate as a moderating variable among Indonesian exporters and freight forwarders using maritime transport and shipping companies also entered into the population to calculate the increase in export volume. A descriptive quantitative method was applied, employing primary data from questionnaires and secondary data from company reports, shipping statistics, and relevant literature. Using purposive sampling and the 10-times rule for 32 indicators, a minimum of 320 respondents was obtained. Data were analyzed with Structural Equation Modeling Partial Least Square (SEM-PLS) using SmartPLS 4. Results reveal that exchange rate, shipping costs, and service quality have a positive and significant impact on export volume. Higher shipping costs accompany increased export activity, while superior service quality enhances efficiency and international trade partner confidence. Conversely, the number of competitors shows no significant effect, indicating that the presence of more shipping operators does not directly raise export shipments. The exchange rate strengthens the relationships between shipping costs and competition with export volume but does not moderate the effect of service quality. These findings highlight the importance of exchange rate stability and improved maritime logistics services to foster Indonesia’s export growth, while expansion of shipping operators should be regulated to ensure competitive pricing and optimal service.